An Actinide Zintl Cluster: A Tris(triamidouranium)μ3‐η2:η2:η2‐Heptaphosphanortricyclane and Its Diverse Synthetic Utility1. Issue 50 (14th October 2013) - Patel, Dipti; Tuna, Floriana; McInnes, Eric J. L.; Lewis, William; Blake, Alexander J.; Liddle, Stephen T.
<x xml:space="preserve">Abstract</x> A diuranium(V) arene complex reductively cleaves P4 to give a triuranium heptaphosphanortricyclane cluster (see picture; U green, P purple, N blue, Si orange). This cluster is the first example of a molecular actinide [P7] Zintl complex and the first example of uranium‐promoted catenation of P4. This complex undergoes a wide range of reactions under mild conditions to afford liberated P7R3 phosphanortricyclanes.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>